Improved gonadal hormones levels following 6 and 12 months of anti-retroviral therapy among men living with human immunodeficiency virus infection. - Shabani Iddi; Haruna Dika; Karol J Marwa; Benson R Kidenya; Samuel E Kalluvya (PLoS ONE)
Background Male hypogonadism is commonly reported in men living with human immunodeficiency virus (HIV) (MLWH), reaching a prevalence of up to 89% and shown to decrease in the antiretroviral therapy (ART) era as compared to pre-ART era. Data regarding the effect of ART on gonadal hormones levels are scarce. We aimed to determine changes in gonadal hormones levels in HIV males following ART initiation. Methods This was a longitudinal study involving newly diagnosed ART naïve MLWH in Mwanza, Tanzania. All enrolled participants underwent thorough clinical and physical examination including anthropometric measurements. A pre-structured questionnaire was used to collect socio-demographic and clinical data. Serum total testosterone (TT), follicle-stimulating hormone (FSH), luteinizing hormone (LH) and estradiol were estimated at baseline, six and twelve months after ART initiation. Serum TT < 300 ng/dl, or ≥300 ng/dl with high LH and FSH were taken as markers of hypogonadism. Data were analyzed using STATA version 15. Results A total of 213 participants were enrolled in this study. Between individual's pairs, the median levels of TT and LH after six and twelve months were found to be significantly higher while estradiol was significantly lower than at baseline (p < 0.001). Between after six and after twelve months, only median estradiol levels showed significant change with levels being lower after twelve months (p < 0.001). The change in FSH was not statistically significant. Of the 89 participants (41.8%) who had hypogonadism at baseline, 44 (49.4%) normalized TT (≥300 ng/ml) and had higher median testosterone than those who did not normalize. Furthermore, there was a statistically significant association between testosterone change and initial viral load (p = 0.049), WHO clinical stage (p = 0.031) and baseline hypogonadism status (p = 0.014). Conclusion This study concludes that TT improved significantly after ART initiation. Particularly, half of the MLWH who presented with low TT at baseline normalized it within the first year of treatment. Therefore, ART reduces prevalence of hypogonadism and baseline TT seems to be predictive of future evolution of the hypogonadism.